Therapeutic Effects of PPARα on Neuronal Death and Microvascular Impairment - Elizabeth P. Moran; Jian-xing Ma (PPAR Research)
Peroxisome-proliferator activated receptor-alpha (PPARα) is a broadly expressed nuclear hormone receptor and is a transcription factor for diverse target genes possessing a PPAR response element (PPRE) in the promoter region. The PPRE is highly conserved, and PPARs thus regulate transcription of an extensive array of target genes involved in energy metabolism, vascular function, oxidative stress, inflammation, and many other biological processes. PPARα has potent protective effects against neuronal cell death and microvascular impairment, which have been attributed in part to its antioxidant and anti-inflammatory properties. Here we discuss PPARα’s effects in neurodegenerative and microvascular diseases and also recent clinical findings that identified therapeutic effects of a PPARα agonist in diabetic microvascular complications.